Development of Critical Thinking Attitude of IPR Students in Learning Indonesian Courses - Siti Badrotil Khasanah; Taufiqurohman Taufiqurohman; Mahmud Arif (Edumaspul: Jurnal Pendidikan, 2023)
One of the potentials that must be developed and formed in higher education is critical thinking. Critical thinking is an organized mental process and plays a role in the process of making decisions to solve problems. Critical thinking includes the activities of analyzing and interpreting data in scientific discovery activities. To develop students' critical thinking skills, learning innovations need to be implemented. The aim of this research is to find out how the critical thinking attitudes of IPR students develop in learning Indonesian language courses. This research is classroom action research using a design developed by Kemmis and MC Taggart which consists of three stages, namely the planning stage, the treatment and observation stage, and the reflection stage. The results of this research show that the development of critical thinking of HKI students in the Indonesian language course has succeeded in improving their thinking skills with a score of 23 in the pre-action stage, cycle I increased to 27.7 and cycle II increased to 36.6.